2021
DOI: 10.3389/fnsys.2020.599781
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane-Induced Burst Suppression Is a Thalamus-Modulated, Focal-Onset Rhythm With Persistent Local Asynchrony and Variable Propagation Patterns in Rats

Abstract: Background: Inhalational anesthetic-induced burst suppression (BS) is classically considered a bilaterally synchronous rhythm. However, local asynchrony has been predicted in theoretical studies and reported in patients with pre-existing focal pathology.Method: We used high-speed widefield calcium imaging to study the spatiotemporal dynamics of isoflurane-induced BS in rats.Results: We found that isoflurane-induced BS is not a globally synchronous rhythm. In the neocortex, neural activity first emerged in a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 61 publications
7
20
0
1
Order By: Relevance
“…The marmoset burst-suppression map is, to our knowledge, the first of its kind and suggests that V1 exclusion may be a general primate feature. The pancortical distribution of burst-suppression in rats agrees with all previous findings in this species, by fMRI (Aedo-Jury et al, 2020;Liu et al, 2013Liu et al, , 2011Paasonen et al, 2019;Schwalm et al, 2017) or calcium imaging (Ming et al, 2021). The strength of our approach lies in computing all maps with the same data-driven approach, thus allowing us to make direct cross-species comparisons.…”
Section: Burst-suppression Across Mammalian Speciessupporting
confidence: 84%
See 2 more Smart Citations
“…The marmoset burst-suppression map is, to our knowledge, the first of its kind and suggests that V1 exclusion may be a general primate feature. The pancortical distribution of burst-suppression in rats agrees with all previous findings in this species, by fMRI (Aedo-Jury et al, 2020;Liu et al, 2013Liu et al, , 2011Paasonen et al, 2019;Schwalm et al, 2017) or calcium imaging (Ming et al, 2021). The strength of our approach lies in computing all maps with the same data-driven approach, thus allowing us to make direct cross-species comparisons.…”
Section: Burst-suppression Across Mammalian Speciessupporting
confidence: 84%
“…The main inter-species difference was the exclusion of visual areas (and parts of other unimodal cortices) in primates, but not in rats. While bursts were traditionally viewed as synchronous cortexwide events, recent work rather describes them as complex waves (Bojak et al, 2015) emerging from a spatially shifting focus and rapidly spreading through the cortex (Ming et al, 2021). Electrocortical recordings in propofol-anesthetized human patients revealed that some electrodes could display continuous activity while others engaged in burst-suppression (Lewis et al, 2013).…”
Section: Burst-suppression Across Mammalian Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the spectral content of recordings from different agents using EMD might prove fruitful in elucidating the differences between the mechanisms underlying different substances. Furthermore, localised presence of burst-suppression has been reported in the literature [32,33]. If different rhythms return at different rates, this might show up as e. g. changes in the origins for individual slow waves.…”
Section: результаты и обсуждениеmentioning
confidence: 80%
“…Изучение спектрального содержания ЭЭГ при применении различных препаратов с помощью РЭМ может оказаться полезным для выяснения различий между механизмами, лежащими в основе их действия. Кроме того, имеются сообщения о локализованном появлении ПВП [32,33]. Если различные ритмы вновь возникают на ЭЭГ после ПВП с разной скоростью, то это может проявиться, например, в виде изменений происхождения ferent suppression durations for underlying neural generators of these spectral components.…”
Section: результаты и обсуждениеunclassified